Insight into the Relationship of Spray-Drying Conditions with the Physicochemical and Gelation Properties of Egg White Protein - Yuying Hu; Yan Hu; Huiyi Wu; Luyang Bao; Xin Shi; Can Wu; Bing Cui; Hongshan Liang; Bin Zhou (Foods)
This study aimed to provide systematic insight into the relationship between spray conditions and the physicochemical and gelation properties of egg white protein (EWP). Specifically, the effects of two key factors, the inlet temperature and flow rate, on the physicochemical and structural properties of EWP were determined. The analysis revealed that as the spray-drying temperature increased, more hydrophobic groups in EWP were exposed and prone to aggregate. Furthermore, the physicochemical and rheological properties and microstructure of egg white protein gel (EWPG) were determined. The results indicate that under a relatively high inlet temperature and a low flow rate, the hardness, springing, and water-holding capacity of the produced gel were improved. Excessively high temperatures were detrimental to pre-aggregate formation and the development of a homogeneous network. The rheological results demonstrate that the EWPG exhibited a weak frequency dependence and elastic-dominant gel characteristics. Further analysis indicated that the inlet temperature significantly influenced the nonlinear response of the EWPG, with the strongest higher-order viscous nonlinear properties observed at 140 °C. The microstructure suggested that at 140 °C, the EWPG achieved a minimum porosity of 50.07% and a maximum fractal dimension (Df) of 2.745, where a uniform network structure was generated. This study demonstrated that relatively high temperatures and low flow rates in the spray-drying process were advantageous for producing egg white protein gel with desirable characteristics, which has potential for the actual application of egg-based food products.